Solve for j 7(j+12k)=g-zq

Math
7(j+12k)=g-zq
Divide each term by 7 and simplify.
Tap for more steps…
Divide each term in 7(j+12k)=g-zq by 7.
7(j+12k)7=g7+-zq7
Cancel the common factor of 7.
Tap for more steps…
Cancel the common factor.
7(j+12k)7=g7+-zq7
Divide j+12k by 1.
j+12k=g7+-zq7
j+12k=g7+-zq7
Move the negative in front of the fraction.
j+12k=g7-zq7
j+12k=g7-zq7
Subtract 12k from both sides of the equation.
j=g7-zq7-12k
Solve for j 7(j+12k)=g-zq

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top